2008
DOI: 10.1111/j.1365-2761.2007.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of cancer in cartilaginous fish: immunocytochemical study of PCNA, p‐53, myc and ras expression in neoplastic and hyperplastic tissues from free ranging blue sharks, Prionace glauca (L.)

Abstract: Archival formalin-fixed tissues from wild-caught adult blue sharks, Prionace glauca (L.), were used for immunocytochemical detection of proliferating cell nuclear antigen (PCNA), two oncoproteins from the oncogenes c-myc and pan-ras, and a protein product from the tumour suppressor gene p-53. All sharks were caught during summer months between 2000 and 2006 by recreational fishermen off the USA coast in the northwestern Atlantic. The sharks were necropsied on landing and selected organ samples were collected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
(60 reference statements)
0
19
1
Order By: Relevance
“…Several studies have indicated that PCNA is a suitable marker for cellular proliferation in fish [39,40] as well as other species [41,42]. However, our study did not indicate any significant differences in PCNA staining among the treatments.…”
Section: Discussioncontrasting
confidence: 89%
“…Several studies have indicated that PCNA is a suitable marker for cellular proliferation in fish [39,40] as well as other species [41,42]. However, our study did not indicate any significant differences in PCNA staining among the treatments.…”
Section: Discussioncontrasting
confidence: 89%
“…The immunopositivities to the two antisera were equivalent; moreover, Western blot analysis on the olfactory organs of S. canicula showed a band with a molecular weight consistent with that of PCNA. The immunodetection of PCNA was previously performed, with good results, on fish (e.g., Bettini et al, 2006Bettini et al, , 2009Ferrando et al, 2005), including specifically elasmobranch (Borucinska et al, 2008;Ferreiro-Galve et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation can be detected by immunohistochemical staining of the proliferating cell nuclear antigen (PCNA) (see [3]), which is an evolutionary, highly conserved 36 kd protein that is directly involved in DNA synthesis [4]. PCNA immuno-positivity is confined largely to the nuclei of dividing sperm cells, in ovarian follicles, lymphoid tissues of the kidneys, in neuronal cells of proliferative regions of the brain, epithelial cells of gill filaments, and, in the proliferative zones in the crypt regions of mucosal folds [5-7]. In teleosts, the presence of these proliferating cells at the base of intestinal folds have been described in Ctenopharyngodon idella (Valenciennes) [8] and in Barbus conchonius (F. Hamilton) [9].…”
Section: Introductionmentioning
confidence: 99%